Geoedupreneurship and Educational Innovation: Exploring the Need for Geography Education-Based Entrepreneurship Learning Materials - Ainun Maghfiroh; Sumarmi Sumarmi; Sugeng Utaya; Adip Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Digital transformation in the Industrial Revolution 5.0 requires higher education to produce graduates who are adaptive, creative, and possess entrepreneurial capacity. Geography education has strategic potential in supporting these goals through a geoedupreneurship approach that integrates spatial literacy and entrepreneurial competencies. This study aims to identify the need for geography education-based entrepreneurship learning materials through a mixed-methods approach, incorporating both quantitative and qualitative descriptive analyses. The results show that 64.3% of students require the integration of real-life case studies, 54.8% desire interactive digital innovation, and 45.2% experience difficulties converting spatial data into business opportunities. These findings highlight the limitations of current learning materials, which remain theoretical and fail to address the contextual needs of 21st-century learning. Based on the analysis results, an adaptive geoedupreneurship learning material model was designed that combines a project-based approach, digital technology, and inspirational narratives as a strategy to strengthen geography-based entrepreneurial competencies that are relevant, applicable, and sustainable